2012
DOI: 10.1021/jp303040m
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption, Co-adsorption, and Reactions of Sulfur Compounds, Aromatics, Olefins over Ce-Exchanged Y Zeolite

Abstract: Adsorption, coadsorption, and reactions of sulfur compounds, olefins, and aromatics over Ce-exchanged Y zeolite (CeY) have been studied by N2 adsorption, intelligent gravimetric analyzers (IGA), X-ray diffraction (XRD), inductively coupled plasma mass spectrometry (ICP-MS), X-ray photoelectron spectroscopy (XPS), high-resolution transmission electron microscopy (HRTEM), Fourier-transform infrared spectroscopy (FT-IR), frequency response (FR) techniques, and batch and fixed bed methods. The coadsorption of olef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 41 publications
2
45
0
Order By: Relevance
“…Several models assumed that the sulfur density is constant and does not change with the reservoir conditions; relating the sulfur density to the reservoir temperature will greatly assist in understanding the mechanism and the phase at which the elemental sulfur will deposit. Fanelli (1950) reported surface-tension measurements for highly purified sulfur. Fanelli found that surface tension decreases linearly with temperature, and there is a distinct discontinuity at approximately 160 C. At temperatures greater than 160 C, the decrease is more gradual.…”
Section: Elemental-sulfur Physical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several models assumed that the sulfur density is constant and does not change with the reservoir conditions; relating the sulfur density to the reservoir temperature will greatly assist in understanding the mechanism and the phase at which the elemental sulfur will deposit. Fanelli (1950) reported surface-tension measurements for highly purified sulfur. Fanelli found that surface tension decreases linearly with temperature, and there is a distinct discontinuity at approximately 160 C. At temperatures greater than 160 C, the decrease is more gradual.…”
Section: Elemental-sulfur Physical Propertiesmentioning
confidence: 99%
“…All the analytical models neglected the adsorption of liquid sulfur by the formation rocks; the adsorption part will be significant if the formation contains some clay because the clay minerals help in the adsorption process. Many authors have mentioned the sulfur adsorption onto different chemical processes (Boulinguiez and Le Cloirec 2010;Duan et al 2012). The sulfur-adsorption term will affect the value of sulfur saturation in the reservoir.…”
Section: Sulfur-adsorption Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…All the analytical models neglected the adsorption of liquid sulfur by the formation rocks, the adsorption part will be significant if the formation contains some clays because the clay minerals help in the adsorption process. Many authors have mentioned the sulfur adsorption onto different chemical processes (Duan et al 2012 andBoulinnguiez, andLe Cloirec 2010). This adsorption term will affect the value of sulfur saturation calculations especially around the wellbore.…”
Section: Analytical Modelsmentioning
confidence: 99%
“…In recent years, the deep desulfurization of fuel has received worldwide attention because of increasingly stringent environmental regulations and environmental protection . At present, oxidative desulfurization (ODS) is considered a sustainable route for moderate operation conditions .…”
Section: Introductionmentioning
confidence: 99%